The Effectiveness of Blended Learning Examined Critical Thinking and Mathematics Learning Independence for High School Students - Aswar Aswar; Ali Mahmudi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study was aimed to describe: (1) the effectiveness of learning with a blended learning model using scientific (2) the effectiveness of scientific approach; and (3) the difference in the effectiveness of learning with a blended learning model using scientific approach and learning using scientific approach in terms of critical thinking, and learning independence of mathematics students in high school. The research type is quasi-experiment. The population was all 11th grade students of SMA in semester II of 2024/2025. The sample was established randomly consisting of class XI MIA 2 as the experiment class and XI MIA 1 as the control class. The data collection method uses research instruments in the form of a Learning Independence Test of 15 multiple choice questions, a Critical Thinking Test of 4 descriptive questions, and a Learning Independence Questionnaire of 20 statement, administered as pretests and posttests. To assess the effectiveness of blended learning with a scientific approach and the scientific approach alone, a one-sample mean vector test was conducted, followed by a one-sample t-test. Differences in effectiveness were analyzed using an independent two-sample mean vector test (T² Hotelling). If analysis revealed significant differences between the two classes, an independent sample t-test for comparison was conducted. The results showed that: (1) learning with blended learning model using scientific approach is effective in terms of critical thinking, and independence of learning mathematics of high school students; (2) learning using scientific approach is effective in terms of critical thinking, and independence of learning mathematics of high school students; and (3) learning with blended learning model using scientific approach is more effective than learning using scientific approach in terms of critical thinking, and independence of learning mathematics of high school students.